Identification of Bioactive Components in Various Purslane Species and Their Potential as Fuctional Food - Alayda Rahma Putri Aditya; Sri Winarti; Hadi Munarko (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Portulaca pilosa. This study aims to identify the chemical and bioactive components of various purslane types and their potential as functional foods. The functional effects analysed include antioxidant activity and in vitro inhibition of ?-amylase. This study used a completely randomized design (CRD) with 3 replicates. The results showed that the chemical and bioactive components differed significantly among purslane species. The bioactive components identified included vitamin C, TDF (total dietary fiber), total phenols, omega-3, omega-6, and omega-9 fatty acids. All purslane flour species contained omega fatty acids dominated by omega-3, particularly ?-linolenic acid (ALA, C18:3 ?-3), omega-6 dominated by linoleic acid (C18:2 ?-6), and omega-9 dominated by oleic acid (C18:1 ?-9c). he antioxidant activity of purslane ranged from 143.64 to 536.03 AAE/100 g, and its ability to inhibit ?-amylase enzyme activity ranged from 64.99 to 82.05%. All purslane flours showed strong ?-amylase inhibitory activity with IC?? ? 50 ?g/mL. These findings indicate that purslane species have high potential as functional food ingredients. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-Being|SDG 12: Responsible Consumption and Production